ADHD subtypes: Do they hold beyond core symptoms? A multilevel testing of an additive model. Issue 3 (3rd July 2022) - Rostami, Mohammad; Khosrowabadi, Reza; Albrecht, Björn; Pouretemad, Hamidreza; Rothenberger, Aribert
Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is characterized as a behavioral syndrome with core symptoms of inattention and/or hyperactivity/impulsivity that constitute, according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), predominantly Inattentive and Hyperactive-Impulsive and a combined (additive) presentation that fulfills both criteria. The question remains if the pathophysiological background of both factors is also separate at levels of investigation beyond core symptoms. This would allow a clearer understanding and a more focused treatment approach even with tools derived from these levels. Hence, we assumed that an implicit additive diagnostic model also holds at the levels of associated psychopathology, neuropsychological performance and brain oscillations. We investigated this hypothesis using data of 61 boys (7–12 years old) with ADHD and 43 typically developing children. There were no significant differences in age and IQ between groups. Children were examined with Child Behavior Checklist (CBCL), the Integrated Visual and Auditory Test (IVA), and brain oscillations during eyes closed resting state. Inattention characteristics were associated with more pronounced internalizing problems, lower attention, and vigilance during IVA performance and at the Electroencephalography level with elevated Theta and diminished Beta power during eyes closed rest. In contrast, hyperactivity/impulsivity characteristics led to general psychopathology problems and showed at the neuropsychological level faster response speed and deficits in cognitive control and performance consistency, but were on the electroencephalography level without any deficits in EEG power. Considering differences in behavioral, neuropsychology, and electroencephalography levels in each subtype, separate clinical approaches should be recommended for them and an additive model for their combination.